具通信功能之車用功率系統晶片---總計畫(I) - 蘇朝琴; SU CHAU-CHIN (My University, 2008)
本計畫提出結合Power IC 與Power Line Communication 的系統晶片設計，提供汽車所 需的電源管理、功率驅動、與資料傳輸。透過本項技術，汽車只需要使用一條電源線，就 可以整合所有的資料傳輸與功率驅動。如此，將會極度的簡化汽車的設計與製作成本。 本計畫的有兩個主要的特色，一是我們採用電源線通信機制 Power Line Communication (PLC)，此一機制有別於家庭用的PLC 如HomePlug，本計畫的目標為由汽 車電池提供的直流電源，它只有一條電源線，迴路由汽車的車架來完成，我們必須要重建 通道模型才能夠決定系統設計的參數。二是我們結合可程式的功率積體電路，根據所接受 的指令，產生所需要的驅動信號，來驅動被控制的元件。給予不同之燈具或驅動馬達其特 有最佳的驅動電壓、電流、與驅動曲線Voltage/Current Profile。 本計畫亦有兩個主要的優勢，由於採用Power Wire Communication，車子的控制線路 完全不需要，大大的簡化汽車組裝的成本。再加上它也具多樣化的驅動能力，因此受驅動 點不需要再有自己的驅動電路，也達到樽節成本的目的。 本計畫分為四個子計畫進行。 子計畫一：搜尋一個車用直流Power Line Communication 的通道模型並據此設計通訊 架構並完成基頻電路設計。 子計畫二：完成一個車用直流Power Line Communication 的類比前端電路以及數位類 比轉換電路，以搭配子計畫一成為一個完整的車用 PLC。 子計畫三：完成一個汽車馬達的驅動的設計，在不同駕駛情境中根據指令動態調整馬 達的驅動能力，以兼具車輛行駛的穩定度與電能消耗的最小化。 子計畫三：完成一個車用可程式功率驅動積體電路，可根據指令調整驅動之電壓、電 流與驅動曲線，以適用於車上多數的電氣設備。

This project integrates power IC and power line communication into an SoC. It provides the needed power management, power driving, and data communication at the same time. With such an technology, a car requires only one power line to integrates all the driving and communication needs. Such that, the design and manufacturing cost can be minimized significantly. There are two distinguishing features in this project. First, the power line communication we use is different from the PLCs used in the home, such as HomePlug. It is battery powered DC power line. It consists of only one line, the return loop is made up by the framework of the car. So that, we needs to measure and build the channel model, which has never been investigated before. With the channel model, the system design parameters can then be determined. Second, the power driving IC is able to produce the optimal voltage or current profile according to the command sent through the PLC. The project technology has the following two advantages. First, due to the use of power line for communication, all the wires, except power lines, can be removed. The assembly cost is significantly reduced. Second, with the programmable divers on chip, the driven nodes no long need its own driving circuitry. As a result, the component cost is also reduced. This project contains four subprojects. Subproject 1: This subproject will survey a channel modeling for the automobile DC power lines, derive the communication algorithm, and implement the baseband circuitry. Subproject 2: This subproject will design the front-end analog and AD/DA converting circuitry according to the specification derived in subproject 1. Subproject 3: This subproject will investigate the driving algorithm for the automobile motors in order to meet the driving requirement and minimize the power consumption. Subproject 4: This subproject will design and implement an programmable power driving IC that can produce needed voltage/current profile according to the command.
Automobile Power SoC with Embedded Power Line Communication(I)
Keywords: 系統晶片; 電源線通訊; 功率積體電路; 馬達驅動; SoC; Power Line Communication; Power IC; Motor Actuator